Estimation of the Lifetime of Bonded Joints under Cyclic Loads at Different Temperatures. Issue 7 (1st September 2016) - Schneider, B.; Beber, V. C.; Brede, M.
Abstract : The fatigue lifetime of joints bonded with a toughened epoxy adhesive has been estimated using the stress-life method, based on experimental SN curves. Five temperatures (35°C, −10°C, RT, +50°C, +80°C) were considered. The estimations were performed using a direct approach, for joints having near-homogeneous stress distributions (scarf joints), and; an optimised approach, for joints having inhomogeneous stress distributions (single lap joints). The stress distributions were calculated considering linear-elastic material behaviour using analytical methods and finite element analysis. For inhomogeneous stress distributions the effective stress was defined in terms of the theory of critical distances. The calculations were performed considering: (i) uniaxial stress, evaluating the maximum principal stress, and considering (ii) multiaxial stress, for the influence of the relationship between hydrostatic and deviatoric stresses. The estimations were validated with fatigue experiments under tension–tension loading at a stress ratio of 0.1 and a frequency of 7 Hz. The experimental results showed a reduction of fatigue lifetime with increasing temperature. The estimated values indicate a better quality of prediction for the multiaxial stress and that it is more preferable to use a base SN curve having a stress distribution as similar as possible to the stress distributions of the components to be designed.